2009
DOI: 10.1111/j.1538-7836.2008.03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in patients with hemophilia

Abstract: Summary.  Mortality due to ischemic heart disease in hemophilia patients is lower as compared to the general male population. Differences in the prevalence of cardiovascular risk factors cannot explain this finding. The hypocoagulable state of hemophilia patients might have a protective effect on thrombus formation, which precipitates infarction. It remains unclear whether the deficiency of coagulation factor VIII or IX exerts a protective effect on the development of atherosclerosis. Despite the relative prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 54 publications
(143 reference statements)
3
109
0
3
Order By: Relevance
“…The availability of replacement factor products and improvements in treatment strategies over time have led to increased life expectancy of patients with hemophilia; consequently, the incidence of age‐related comorbidities has increased in this population 1, 2. There have been conflicting published data regarding the risks of cardiovascular (CV) comorbidities in patients with hemophilia compared with the general population.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The availability of replacement factor products and improvements in treatment strategies over time have led to increased life expectancy of patients with hemophilia; consequently, the incidence of age‐related comorbidities has increased in this population 1, 2. There have been conflicting published data regarding the risks of cardiovascular (CV) comorbidities in patients with hemophilia compared with the general population.…”
Section: Tablementioning
confidence: 99%
“…There have been conflicting published data regarding the risks of cardiovascular (CV) comorbidities in patients with hemophilia compared with the general population. Some studies have reported lower mortality from CV diseases and/or decreased atherogenesis in patients with hemophilia because of the potentially protective effect of chronically low factor VIII (FVIII) activity on thrombus formation 2, 3. Conversely, other reports indicate comparable or higher CV comorbidities in patients with hemophilia compared with the general population 4, 5, 6.…”
Section: Tablementioning
confidence: 99%
“…In human studies, genetic factors that clearly increased risk of VTE only slightly increased risk for MI (2032). Similarly, carrying an allele for a bleeding disorder may only slightly decrease risk for MI, if at all (1628,1667,1668,1820). Despite these caveats, a number of new animal models of thrombosis-related genes present promising new avenues for research into this late stage of atherogenesis (see TABLE 10) (183).…”
Section: B Thrombosis and Atherosclerosismentioning
confidence: 99%
“…Tuinenburg et al 48 showed that the standard mortality ratio (calculated by dividing the number of observed deaths by those expected in the general population) ranged from 0.2 to 0.6 in PWHs in the time period spanning from 1989 to 2006. 48 On the other hand, coronary artery and other atherothrombotic diseases do indeed occur in PWHs, as it stems from a review on the causes of death in PWHs, 49 from a review article based on 42 cases 50 and the experiences gained in our large tertiary-care centers. This is not unexpected because if, on one hand, PWHs may be protected from thrombus formation by their hypocoagulability, on the other hand, they are exposed at least as much as normal males to such risk factors for atherosclerosis as aging, smoking, and overweight.…”
Section: Cardiovascular Diseasementioning
confidence: 99%